Meningkatkan Keterampilan Membaca Pemahaman Menggunakan Media Flipbook Digital bagi Siswa dengan Hambatan Pendengaran - Ranisa, Irfa Dillah; Efrina, Elsa; Marlina, Marlina; Mahdi, Arisul (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to improve the reading comprehension skills of students with hearing impairments through the use of digital flipbook media. The research used a quantitative approach with an experimental method in the form of Single Subject Research (SSR) using an A–B–A design consisting of an initial baseline phase (A₁), an intervention phase (B), and a final baseline phase (A₂). The research subject was one fifth-grade student with hearing impairment. Data collection was conducted through reading comprehension skill tests using instruments in the form of checklists compiled based on reading comprehension indicators. The data were analysed using visual graphic analysis by comparing the percentage of reading comprehension skills in each phase to see the trend of change and data stability. The results showed an increase in reading comprehension skills after the intervention using the Digital Flipbook media, as indicated by the difference in achievement levels between the baseline and intervention phases. Thus, the Digital Flipbook media proved to be effective in improving the reading comprehension skills of fifth-grade students with hearing impairments at SLB Negeri 1 Lubuk Sikaping